ANALYSIS OF THE DEVELOPMENT OF THE PROCESSING INDUSTRY AGRICULTURE VINNYTSIA REGION - Mariya Varlamova (European Cooperation, 2015)
The article investigates the current state of the processing industry of agro-industrial complex in Vinnytsia region. Analyzed dynamics of production of main kinds of products of the processing of the agricultural sector. Definition of the sphere of processing industry, in which there is underutilization of production capacity in comparison to previous periods. Activities aimed at enhancing their development will contribute to the increase in the proportion of products Vinnytsia oblast in the Ukrainian market. Improving the competitiveness of the processing industry of the region is possible by switching production to innovative model of development. The purpose of using the potential and the increase of production volumes of processing of agriculture Vinnytsia region prompted the creation of a strategy for the management of investment and innovative activity in agrarian and industrial complex focused on increasing investment and innovation activity of enterprises of processing industry. The structure of this strategy. Through the development of regional strategies should be formed strategy of investment and innovation development of the processing industry across the country